Identification and diversity of Fusarium species isolated from tomato fruits - Abd Murad, Nur Baiti; Kusai, Nor Azizah; Mohd Zainudin, Nur Ain Izzati (De Gruyter Open, 2016)
Fruit rot of tomato is a serious disease caused by Fusarium species. Sampling was conducted throughout Selangor, Malaysia and fungal species identification was conducted based on morphological and gene encoding translation elongation factor 1-α (tef1-α) sequence analysis. Five species of Fusarium were discovered namely F. oxysporum (including F. oxysporum f. sp. lycopersici), F. solani, F. equiseti, F. proliferatum and F. verticillioides. Our results provide additional information regarding the diversity of Fusarium species associated with fruit rot disease of tomato.